PENGARUH PIJAT DEEP BACK MASSAGE TERHADAP NYERI PERSALINAN PADA FASE AKTIF TAHAP PERTAMA PERSALINAN PADA WANITA YANG MELAHIRKAN - Hernawati, Yeti; Elisa, Rina; Triwidiyantari, Dyah; Rosita, Rosita (Sekolah Tinggi Ilmu Kesehatan Dharma husada, 2026)
Background: Labor is a physiological process commonly accompanied by pain, which may lead to traumatic experiences and anxiety; appropriate non-pharmacological pain management, such as Deep Back Massage, may help mothers feel calmer and more relaxed. Methods: This study employed a quasi-experimental design with a pretest–posttest control group approach among mothers in the active phase of the first stage of labor at Bandung Kiwari Regional Public Hospital, Bandung City. Data were analyzed using univariate and bivariate analysis. Results: The administration of Deep Back Massage showed a significant effect in reducing labor pain intensity among mothers in the active phase of the first stage of labor. Conclusion: Deep Back Massage is effective in reducing labor pain during the active phase of the first stage of labor and can be implemented as a non-pharmacological method for pain management during childbirth.